First report of a new bipartite geminivirus isolated from tomatoes in Cuba - Martinez Zubiaur, Y.=700 1 De Blas, C.; Peralta, E.L.; Zabalgogeazcoa, I.; Quiñones, M.; Castellanos, C.; Malpica, J.; Romero, J.
(Es, En)
Ilus., 12 ref.
Keywords: TOMATE; GEMINIVIRUS; TRANSMISION DE ENFERMEDADES; VIRUS; ALEYRORIDAE; CUBA; MOSCA BLANCA; REVISTA DE PROTECCION VEGETAL